Simultaneous and sequential contributions to step-level public goods: One vs. two provision levels - Hans-Theo Normann; Holger A. Rau (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
In a step-level public-good experiment, we investigate how the order of moves (simultaneous vs. sequential) and the number of step levels (one vs. two) affects public-good provision in a two-player game. We find that the sequential order of moves significantly improves public-good provision and payoffs, even though second movers often punish first movers who give less than half of the threshold contribution. The additional second step level - which is not feasible in standard Nash equilibrium - leads to higher contributions but does not improve public-good provision and lowers payoffs. We calibrate the parameters of Fehr and Schmidt's (1999) model of inequality aversion to make quantitative predictions. We find that actual behavior fits remarkably well with several predictions in a quantitative sense.
Keywords: C92; D70; H41; 330; experimental economics; fund raising; provision-point public good; sequential play; threshold public good